Analysis of the Potential Hazard Identification and Risk Assessment (HIRA) and Hazard Operability Study (HAZOP): Case Study - Suhardi, Bambang; Widyo Laksono, Pringgo; Ayu V.E, Andhika; Mohd.Rohani, Jafri; Shy Ching, Tan (International Journal of Engineering and Technology, 2018)
This study aims to investigate the potential hazards and accidents that might occur at batik printing PT. Batik Merak Manis and recommends practical solutions to enhance safety and health at the workplace. This research adopts Hazard Identification Risk Assessment (HIRA) and Hazard and Operability Studies (HAZOP) to perform risk identification and assessment in the workplace. There are 17 findings of potential hazards in the production areas of batik printing which can be categorized into five types of hazards including: workers attitude, work posture, work procedure, workstation, and physical work environment. Of the risk assessment, the obtained value of 34% in the category of extreme hazard, 24% hazard in the high and medium category respectively, and 18% lower hazard category. Proposed improvements are made based HAZOP analysis worksheet. The proposed practical solutions include improvements in work attitude, work posture, and physical work environment.Â